2021
DOI: 10.1155/2021/6661193
|View full text |Cite
|
Sign up to set email alerts
|

Development of Coconut Milk-Based Spicy Ice Cream as a Nondairy Alternative with Desired Physicochemical and Sensory Attributes

Abstract: Spices have been a major influence on Sri Lankan cuisine since times immemorial. Spices are identified as one of the most distinctive ingredients for their indigenous flavor, aroma, and medicinal properties. In this study, coconut milk-based spicy ice cream was developed in compliance with the Sri Lankan standards to introduce a new perception of flavor using spices to the ice cream industry. Although coconut ice cream is commercially available in the local market, spicy flavored coconut ice cream is not yet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…There was observed increasing trend in scores of colour, smoothness and mouthfeel of all samples. Sensory evaluation of ice cream samples prepared with different vegan sources such as soy milk, coconut residue, hazelnut milk, watermelon seed flour and soyabean temph flour (Góral et al ., 2018; Kausar & Hassan, 2020; Su'i et al ., 2020; Atalar et al ., 2021; Hanafi et al ., 2021; Perera & Perera, 2021) also indicated the sensory results in agreement with current findings. Vegan ingredients proved effective and partially suitable alternatives of dairy ingredients in sense of physicochemical and sensory quality of finished products.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…There was observed increasing trend in scores of colour, smoothness and mouthfeel of all samples. Sensory evaluation of ice cream samples prepared with different vegan sources such as soy milk, coconut residue, hazelnut milk, watermelon seed flour and soyabean temph flour (Góral et al ., 2018; Kausar & Hassan, 2020; Su'i et al ., 2020; Atalar et al ., 2021; Hanafi et al ., 2021; Perera & Perera, 2021) also indicated the sensory results in agreement with current findings. Vegan ingredients proved effective and partially suitable alternatives of dairy ingredients in sense of physicochemical and sensory quality of finished products.…”
Section: Resultssupporting
confidence: 91%
“…temph flour(G óral et al, 2018;& Hassan, 2020;Su'i et al, 2020;Atalar et al, 2021; Hanafi et al, 2021;Perera & Perera, 2021) also indicated the sensory results in agreement with current findings. Vegan ingredients proved effective and partially suitable alternatives of dairy ingredients in sense of physicochemical and sensory quality of finished products.…”
supporting
confidence: 88%
“…Coconut milk is a creamy, whitish liquid that is obtained from the grated kernel of a fresh coconut ( Cocos nucifera ) either by manual or mechanical means . It is a famous beverage and is widely applied as a food ingredient in various sweet and savory recipes in the Indian subcontinent and Southeast Asia. , Coconut milk has a high fat content and is a good source of calcium, iron, zinc, magnesium, and potassium.…”
Section: Plant-based Dairy Alternatives For Ice Cream Applicationmentioning
confidence: 99%
“…39,40 Additionally, the inclusion of coconut milk increases the mineral content and antioxidant activities of ice cream. 39,40 Ice cream prepared using coconut milk has been shown to have improved foam stability, textural parameters, overrun, melting time, and consistency compared to cow's milk ice cream. 32,37,38,41,42 7.1.3.…”
Section: Plant-based Dairy Alternatives For Ice Cream Applicationmentioning
confidence: 99%
See 1 more Smart Citation